Transmissibility Matrix in Harmonic and Random Processes - M. Fontul; A.M.R. Ribeiro; J.M.M. Silva; N.M.M. Maia (Shock and Vibration)
The transmissibility concept may be generalized to multi-degree-of-freedom systems with multiple random excitations. This generalization involves the definition of a transmissibility matrix, relating two sets of responses when the structure is subjected to excitation at a given set of coordinates. Applying such a concept to an experimental example is the easiest way to validate this method.